Progression and treatment rates using an active surveillance protocol incorporating image‐guided baseline biopsies and multiparametric magnetic resonance imaging monitoring for men with favourable‐risk prostate cancer. (8th March 2018) - Thurtle, David; Barrett, Tristan; Thankappan‐Nair, Vineetha; Koo, Brendan; Warren, Anne; Kastner, Christof; Saeb‐Parsy, Kasra; Kimberley‐Duffell, Jenna; Gnanapragasam, Vincent J.
Abstract : Objective: To assess early outcomes since the introduction of an active surveillance (AS) protocol incorporating multiparametric magnetic resonance imaging (mpMRI)‐guided baseline biopsies and image‐based surveillance. Patients and Methods: A new AS protocol mandating image‐guided baseline biopsies, annual mpMRI and 3‐monthly prostate‐specific antigen (PSA) testing, but which retained protocol re‐biopsies, was tested. Pathological progression, treatment conversion and triggers for non‐protocol biopsy were recorded prospectively. Results: Data from 157 men enrolled in the AS protocol (median age 64 years, PSA 6.8 ng/mL, follow‐up 39 months) were interrogated. A total of 12 men (7.6%) left the AS programme by choice. Of the 145 men who remained, 104 had re‐biopsies either triggered by a rise in PSA level, change in mpMRI findings or by protocol. Overall, 23 men (15.9%) experienced disease progression; pathological changes were observed in 20 men and changes in imaging results were observed in three men. Of these 23 men, 17 switched to treatment, giving a conversion rate of 11.7% (<4% per year). Of the 20 men with pathological progression, this was detected in four of them after a PSA increase triggered a re‐biopsy, while in 10 men progression was detected after an mpMRI change. Progression was detected in six men, however, solely after a protocol re‐biopsy without prior PSA or mpMRI changes. Using PSA and mpMRI changes alone to detect progression was found to have a sensitivity and specificity of 70.0% and 81.7%, respectively. Conclusion: Our AS protocol, with thorough baseline assessment and imaging‐based surveillance, showed low rates of progression and treatment conversion. Changes in mpMRI findings were the principle trigger for detecting progression by imaging alone or pathologically; however, per protocol re‐biopsy still detected a significant number of pathological progressions without mpMRI or PSA changes.